2014
DOI: 10.1186/1477-7827-12-50
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of development and regulation of endometriosis

Abstract: Endometriosis is a common and painful condition affecting women of reproductive age. While the underlying pathophysiology is still largely unknown, much advancement has been made in understanding the progression of the disease. In recent years, a great deal of research has focused on non-invasive diagnostic tools, such as biomarkers, as well as identification of potential therapeutic targets. In this article, we will review the etiology and cellular mechanisms associated with endometriosis as well as the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 232 publications
1
91
1
3
Order By: Relevance
“…Increasing evidence supports endometriosis as a complex polygenic and multifactorial disease, caused by multiple genetic and environmental factors acting in concert [16,17]. Recently, several genome-wide association studies have demonstrated an association between endometriosis and markers located in or near to WNT4 gene [8][9][10].…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence supports endometriosis as a complex polygenic and multifactorial disease, caused by multiple genetic and environmental factors acting in concert [16,17]. Recently, several genome-wide association studies have demonstrated an association between endometriosis and markers located in or near to WNT4 gene [8][9][10].…”
Section: Discussionmentioning
confidence: 98%
“…Activated MAPK coordinates diverse cellular activities including cellular metabolism, differentiation, cell cycle, motility, apoptosis, and survival. One of the MAPKs, ERK1/2, has been suggested as a key regulator of the majority of the signalling pathways and cascades associated with the pathogenesis of endometriosis [38]. For example, some factors in the endometriotic milieu such as tumour necrosis factor α (TNFα) and monocyte chemotactic protein-1 (MCP-1) have been shown to regulate ERK signalling in endometriotic cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of women with endometriosis during reproductive years reaches 10%, and those who have pelvic or infertility are more likely to suffer from endometriosis . Although, a previous report indicated that the prevalence of endometriosis had decreased in a certain degree, the incidence of endometriosis was higher than several decades ago . A great deal of health‐care resources and persistent therapy are needed for the patients with endometriosis, since once the current medical therapies are discontinued, the alleviative symptoms are likely to recur and extra interventions are required .…”
Section: Introductionmentioning
confidence: 99%